2018
DOI: 10.1111/modl.12516
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Connections Between First and Second Language Fluency: A Mixed Methods Approach

Abstract: Many factors influencing second language (L2) speech fluency have been widely studied, but the effects of first language (L1) fluency on L2 speech fluency are still relatively poorly understood. In contrast to mostly quantitative previous studies, the present study adopted a mixed methods approach to examining the connections between L1 fluency and L2 fluency. Monologue speech samples in L1 and L2 were obtained from 42 Finnish learners of English at 2 school levels (9th grade and upper secondary school). The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
40
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 49 publications
9
40
1
2
Order By: Relevance
“…The high correlation obtained for mid-clause filled pauses, however, suggests that L2 pausing behavior in the current study is also to some extent a function of one's personal style carried over from L1 behavior. Overall, these findings corroborate the findings of previous research (de Peltonen, 2018) regarding the correlations between breakdown measures in L1 and L2.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The high correlation obtained for mid-clause filled pauses, however, suggests that L2 pausing behavior in the current study is also to some extent a function of one's personal style carried over from L1 behavior. Overall, these findings corroborate the findings of previous research (de Peltonen, 2018) regarding the correlations between breakdown measures in L1 and L2.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed significant positive correlations for three breakdown measures, that is, number of mid-clause filled pauses (r = .60), number of end-clause filled pauses (r = .31), and number of mid-clause silent pauses (r = .35), suggesting that the L2 speakers' frequency of pausing was to some extent a function of their L1 pausing behavior. These correlations replicate the findings of Peltonen (2018) in which moderate to high correlations of (r = .66) and (r = .41) were reported for mid-clause silent pauses and mid-clause filled pauses. Interestingly, the highest correlation found in our results is for mid-clause filled pauses (r = .60), indicating a high degree of association between L1 and L2 pausing behavior.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…L1-L2 relationship in utterance fluency L1 speakers are often assumed to talk fluently by default (Riggenbach, 1991); however, individual differences in terms of temporal aspects of speech have been documented (e.g., Goldman-Eisler, 1968;Shriberg, 1994). Some previous studies on L2 fluency have further shown that certain aspects of L2 utterance fluency are correlated with those of L1 utterance fluency (e.g., de Jong et al, 2015;Huensch & Tracy-Ventura, 2017;Peltonen, 2018). For instance, de Jong et al (2015) examined to what extent L2 utterance fluency measures are reliable indicators of L2 proficiency given that fluency is also influenced by personality or speaking style.…”
mentioning
confidence: 99%
“…For example, while composite measures correspond more strongly with human judgement of fluency (e.g., Kormos & Denes, ), pure measures tell us more about the underlying processes of speech formulation and production (e.g., Huensch & Tracy–Ventura, ) and can therefore provide a more nuanced picture of fluency that is more appropriate in language teaching and assessment (Tavakoli & Hunter, ). From a psycholinguistic perspective, an in‐depth and detailed analysis of L2 fluency is also perceived as crucial, since the emerging evidence (de Jong et al., ; Derwing et al., ; Huensch & Tracy–Ventura, ; Peltonen, ) suggests that first language (L1) and L2 fluency behaviors are, at least to some extent, related, and that certain aspects of L2 fluency might be a function of L1 personal styles. In sum, then, given this complex picture, it can be argued that conceptualizing and measuring fluency at a fine‐grained level can not only reveal more about the connection between L2 speech and the underlying speech production processes (Huensch & Tracy–Ventura, ; Hunter, ; Tavakoli & Hunter, ), but it will also enhance a more reliable understanding of what characterizes fluency at different levels of proficiency, making speaking‐test rating scales more useful and meaningful for users and examiners (Nakatsuhara, ; Tavakoli, Nakatsuhara, & Hunter, ).…”
mentioning
confidence: 99%